(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
One of the aims of literary text is to say as much as possible as briefly as possible,means to say more in few words to achieve a maximumeffectiveness. In this case, figuresof speech, specifically symbol, metaphor and simile have an important role, as theyinclude figurative meaning of words besides their literary meaning. In this article, representation, metaphors and similes in George Orwell’s „Animal Farm‟ were studied to find out the effect of using figures of speech on the writer’s style and the addressee’sunderstanding. For this aim, these three figures of speech were founded in the novel andtheir types were determined according to New mark’s (1988b), Fromilhague`s (1995) andRokni `s (2009)classifications, respectively.